Spatial-temporal disparities and influencing factors of total-factor green use efficiency of industrial land in China. (10th January 2019) - Xie, Hualin; Chen, Qianru; Lu, Fucai; Wang, Wei; Yao, Guanrong; Yu, Jiangli
Abstract: Achieving "green" use of industrial land is beneficial to save precious land resources, protect ecological environments and achieve the green development of China's economy. In this paper, we estimate the dynamic performance of the total-factor green use efficiency of industrial land (TGUEIL) in China by using a global non-radial directional distance function (GNDDF) and the non-radial Malmquist performance of industrial land green use (NMPILGU). The results show that the TGUEIL had a rising trend in most years during 2006–2015. The eastern region enjoys the greatest TGUEIL, and the gaps in the TGUEIL between regions are narrowing. Technical progress in the industrial sector contributes more to the NMPILGU than efficiency progress. To raise the TGUEIL, we should increase the internal expenditures in R&D activities, the number of effective inventions and R&D staffs in industrial enterprises. We should promote the use of clean energy in industrial production and increase efforts in energy-saving and emission reduction. We should prohibit local governments from selling land to cover the deficit. The government should pay more attention to industrial labor redundancy in eastern China and guide orderly redundant industrial labor force transfer from eastern regions to central and western regions.